Ethanol-induced cerebellar transcriptomic changes in a postnatal model of fetal alcohol spectrum disorders: Focus on disease onset - Holloway, Kalee N.; Douglas, James C.; Rafferty, Tonya M.; Majewska, Ania K.; Kane, Cynthia J. M.; Drew, Paul D. (Frontiers in Neuroscience, 2023)
Fetal alcohol spectrum disorders (FASD) are a group of neurodevelopmental disorders caused by ethanol exposure in utero, which can result in neurocognitive and behavioral impairments, growth defects, and craniofacial anomalies. FASD affects up to 1-5% of school-aged children in the United States, and there is currently no cure. The underlying mechanisms involved in ethanol teratogenesis remain elusive and need greater understanding to develop and implement effective therapies. Using a third trimester human equivalent postnatal mouse model of FASD, we evaluate the transcriptomic changes induced by ethanol exposure in the cerebellum on P5 and P6, after only 1 or 2 days of ethanol exposure, with the goal of shedding light on the transcriptomic changes induced early during the onset and development of FASD. We have highlighted key pathways and cellular functions altered by ethanol exposure, which include pathways related to immune function and cytokine signaling as well as the cell cycle. Additionally, we found that ethanol exposure resulted in an increase in transcripts associated with a neurodegenerative microglia phenotype, and acute- and pan-injury reactive astrocyte phenotypes. Mixed effects on oligodendrocyte lineage cell associated transcripts and cell cycle associated transcripts were observed. These studies help to elucidate the underlying mechanisms that may be involved with the onset of FASD and provide further insights that may aid in identifying novel targets for interventions and therapeutics.